PENDIDIKAN POLITIK UPAYA MEDORONG PARTISIPASI PEMILIH PEREMPUAN DALAM MENGHADAPI PEMILU 2024 - Rahayu, Zona Rida; Kobal , Hardinalis (PUAN INDONESIA, 2025)
The presentation of community service on political education efforts to increase female voter participation in the 2024 election needs to be done. This is based on the number of female and male voters which is almost the same, with the assumption that female voters are more loyal, and there are few female regional head candidates. This activity was carried out in the form of a workshop. Attended by 100 participants from Solok Regency representing Yasinan groups, gymnastics clubs, Community leaders-Bundo Kandunga, and PAUD teachers. This activity was held on December 23, 2023 at the Premier Hotel, Solok City. This political education is important to be given to all voters, especially female voters. This is because it is necessary to pay attention to the principles of justice and gender equality which are aimed at increasing political participation and women's initiatives, as well as increasing independence and maturity in national and state life. There are several driving factors in efforts to increase female voter participation. These factors include affirmative policies, gender education and awareness, support from non-governmental organizations, social and cultural change, and networking and mentoring. Efforts to increase women's political participation require effective strategies that can be applied in various political situations. First, improving education and political awareness. Second, is building networks and alliances. Third, providing ongoing guidance and services.